2018
DOI: 10.1007/s10856-018-6122-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction toxicity of Amphotericin B through loading into a novel nanoformulation of anionic linear globular dendrimer for improve treatment of leishmania major

Abstract: Amphotericin B (A) as an antileishmanial drug has limited clinical application owing to severe side-effects and low-water solubility. This is the first study reported using Anionic Linear Globular Dendrimer (ALGD) as A carrier for the increase of A solubility rate, decrease its toxicity, and improve its therapeutic effects. ALGD was synthesized and A was loaded into nanoparticles for the first time with the drug-loading efficiency of 82%. Drug loading was confirmed using characterization methods. The drug solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…However, they demonstrated an only negligible effect on inhibiting parasite in vivo environment, which is possibly due to a low dose of AK1 mg/kg (7- 10,12,13,15,16,24). In the present study, A was loaded into K synthesized by phase separation method (different from previous studies by using ionic gelation) and it was found that K decreased the toxicity effects of A and increased its solubility (14,18). As in previous studies, AK was not effective in inhibiting parasite in vivo in current dosage (1 mg/kg), then we increased the therapeutic dose of AK to 10 mg/kg by using phase separation method and a novel solvent (14).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…However, they demonstrated an only negligible effect on inhibiting parasite in vivo environment, which is possibly due to a low dose of AK1 mg/kg (7- 10,12,13,15,16,24). In the present study, A was loaded into K synthesized by phase separation method (different from previous studies by using ionic gelation) and it was found that K decreased the toxicity effects of A and increased its solubility (14,18). As in previous studies, AK was not effective in inhibiting parasite in vivo in current dosage (1 mg/kg), then we increased the therapeutic dose of AK to 10 mg/kg by using phase separation method and a novel solvent (14).…”
Section: Discussionmentioning
confidence: 59%
“…In the present study, A was loaded into K synthesized by phase separation method (different from previous studies by using ionic gelation) and it was found that K decreased the toxicity effects of A and increased its solubility (14,18). As in previous studies, AK was not effective in inhibiting parasite in vivo in current dosage (1 mg/kg), then we increased the therapeutic dose of AK to 10 mg/kg by using phase separation method and a novel solvent (14). Our findings revealed that parasites were significantly inhibited in our mice model.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Dendrimers as DDS can improve key points in transport and biodistribution such as prolongation of the drug circulation time, enhance drug solubility, enhance tumor permeation and retention, protection of the drug from surroundings, and the ability to target diseased tissue, among others. As a strategy to minimize the cytotoxicity of PAMAM dendrimers, the positive surface charge of its surface has been modified with carboxymethyl chitosan (CMCS) [90][91][92]. Considering that, CMCS is an amphoteric polymer, sensitive pH, and taking doxorubicin as a model drug for cancer, it is that the formulation of a nanoparticle between PAMAM dendrimer and CMCS based on electrostatic conjugation, can transport the drug and release it into the target tissue ( Figure 3A).…”
Section: Dendrimers To Drug Delivery Systems Applicationsmentioning
confidence: 99%